2015
DOI: 10.1007/s10661-015-4887-6
|View full text |Cite
|
Sign up to set email alerts
|

Holding-time and method comparisons for the analysis of fecal-indicator bacteria in groundwater

Abstract: As part of the US Geological Survey National Water-Quality Assessment Program, groundwater samples from domestic- and public-supply wells were collected and analyzed for fecal-indicator bacteria. A holding time comparison for total coliforms, Escherichia coli, and enterococci was done by analyzing samples within 8 h using presence/absence methods and within 18-30 h using quantitative methods. The data indicate that results obtained within 18-30 h were not significantly different from those obtained within 8 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The study also supported the conclusion that sample storage could be extended to 24 h for analysis of microorganisms without altering the mean levels of E. coli, which is in accordance with the results of this paper. Another similar study [21] supported the results reported in this study, stating that extending sample holding time from 8 to 30 h does not affect the bacterial population and also mentioned the possibility to extend sample storage time to 62 h [22]. Extending sampling holding period promotes water testing by making it easier to access certified laboratories in the region through overnight shipment, coordination of delivery with other growers, or transporting by self.…”
Section: Resultssupporting
confidence: 86%
“…The study also supported the conclusion that sample storage could be extended to 24 h for analysis of microorganisms without altering the mean levels of E. coli, which is in accordance with the results of this paper. Another similar study [21] supported the results reported in this study, stating that extending sample holding time from 8 to 30 h does not affect the bacterial population and also mentioned the possibility to extend sample storage time to 62 h [22]. Extending sampling holding period promotes water testing by making it easier to access certified laboratories in the region through overnight shipment, coordination of delivery with other growers, or transporting by self.…”
Section: Resultssupporting
confidence: 86%
“…Enzyme activity assays [7,22,26,28,[42][43][44]77,82,[99][100][101][102][103][144][145][146][147][148][149][150] The assays use enzyme chemistry and are used within biosensors and find results through fluorescence. Additionally, used in portable field kits, automated instruments, and traditional laboratory techniques.…”
Section: Measurement-type Methodsmentioning
confidence: 99%
“…These processes required filtration, selective media, defined substrate technology, and specific reagents. Bushon et al [101] performed a holding time comparison for Colilert and Enterolert by analysing samples within 8 h using presence and absence detection methods and within 18-30 h using quantitative methods. They determined that the results for the Enterolert method was not significantly different; however, for Colilert, the quantitative laboratory methods for samples analysed within 18-30 h showed a statistically significantly higher detection frequency than the presence and absence detection method for analysis within 8 h. They identified that result times were at a minimum within 8 h but Colilert had better results within 18-30 h; and that both methods required multiple processing steps, which limited the efficiency [101].…”
Section: Enzyme Activity Assays and Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation